EKSPLORASI POTENSI ANTIBAKTERI DAUN PIDADA MERAH (SONNERATIA CASEOLARIS) TERHADAP BAKTERI PENYEBAB JERAWAT PROPIONIBACTERIUM ACNES - Eka Kumalasari; Rizki Arianto; Dwi Rizki Febrianti; Novia Ariani; Muhammad Ma'ruf (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Acne that appears on the face can cause changes in the form of swelling, redness, pus and cause pain so that it will cause an impression that is less attractive in appearance and affects beauty. One of the causes of acne is due to the activity of Propionibacterium acnes bacteria. Pidada Merah leaves are one of the plants that contain antibacterial compounds. It is said to contain compounds as antibacterial because it contains secondary metabolites including flavonoids, alkaloids, tannins, saponins, and phenols. The purpose of this study was to determine the antibacterial activity and the diameter of the inhibition zone of Pidada Merah leaf extract against the growth of Propionibacterium acnes.This type of research is not experimental using the well method. This study was divided into seven groups; the extract group with various concentrations (20%, 40%, 60%, and 80%), the positive control group (clindamycin 0.1%) and the negative control group (Aquadest). The results showed that the Pidada Merah leaf extract had antibacterial activity against the growth of Propionibacterium acnes. The diameter of the inhibition zone formed at concentrations of 20%, 40%, 60%, and 80%, respectively 11.51 mm (strong), 11.73 mm (strong), 12 mm (strong), 12.4 mm (strong).